PAIN RELIEF: A LITERATURE REVIEW OF SITZ BATH FOR HEMORRHOID TREATMENT: MENGHILANGKAN RASA SAKIT: TINJAUAN LITERATUR SITZ BATH UNTUK PENGOBATAN HEMOROID - Dewi Ajeng Framesti; Jidan Maulidin Altamimi; Muhammad Ghifari Firdaus; Afianti Sulastri; Nadia Sintia Wardany; Dhika Dharmasyah (Jurnal Kesehatan Tujuh Belas (Jurkes TB), 2025)
Hemorrhoids are an anorectal disorder caused by the dilation and inflammation of blood vessels in the hemorrhoidal plexus, classified into external and internal hemorrhoids, with risk factors such as lifestyle, physical activity, and a history of pregnancy and childbirth, where one of the commonly used therapeutic methods is a sitz bath or warm water therapy, which is believed to relieve pain, reduce inflammation, and accelerate healing, so this study aims to systematically review the effectiveness of this therapy through a Systematic Literature Review (SLR) by searching articles in the PubMed, Mendeley, and Google Scholar databases (2020–2025), analyzed using the PRISMA procedure, where research findings indicate that warm water therapy is effective in reducing pain after hemorrhoidectomy and accelerating healing, while some studies also reveal additional benefits from the use of herbal ingredients and menthol oil in this therapy, although variations in research results highlight the need for further studies with more rigorous methodologies and larger sample sizes, leading to the conclusion that warm water therapy is a non-invasive method that can be used as an alternative in the management of hemorrhoids,